Effects of The Nursing Program on The Practical Knowledge and Disability of Patients with Lumbar Spondylosis Receiving Surgery - Chetwittayachan, Nanrawee; Sukadaecha, Rungrat (Princess of Naradhiwas University Journal, 2026)
Background and Objectives Lumbar spondylosis disease is a health problem that affects disability and requires intervention from healthcare professionals. Therefore, effectively implementing a nursing program for postoperative patients is crucial. This research aimed to compare the practical knowledge and disability levels in patients with lumbar spondylosis disease before and after receiving the nursing program. Methods This study was a single-group quasi-experimental study with pre- and post-intervention measurements. The sample consisted of patients who underwent spinal surgery at Bangkok Hospital Ratchasima. A simple random sample of 26 individuals who met the inclusion criteria was selected. The research team developed a nursing program as an intervention tool for patients undergoing spinal surgery. The content was validated by three experts. The program included four activities: preoperative education, home care instructions, a home visit call, and visit monitoring at the spinal and joint center. The data collection tools included a practical knowledge questionnaire, which had an IOC value > 0.67 and a KR-20 reliability coefficient of 0.709, as well as a disability questionnaire that had a Cronbach’s alpha coefficient of 0.912. Data were analyzed using frequency, percentage, mean, standard deviation, and paired t-test statistics. Results Research findings indicated that 1) the average score for the practical knowledge among patients with lumbar spondylosis who underwent surgery before receiving the nursing program (M=11.730, SD=3.143) was lower than the average score for the practical knowledge after receiving the nursing program (M=17.423, SD=1.447). When comparing the average scores for the practical knowledge in patients with lumbar spondylosis disease who underwent surgery before and after receiving the nursing program, a statistically significant difference was found at the .001 level (t = -9.114, p < .001). 2) The average disability score for patients with lumbar spondylosis disease who underwent surgery before receiving the nursing program (M = 28.807, SD = 8.352) was higher than the average disability score after receiving the nursing program (M = 10.153, SD = 7.603). When comparing the average disability scores of patients with lumbar spondylosis disease who underwent surgery before and after receiving the nursing program, a statistically significant difference was found at the .001 level (t = 10.009, p < .001). Conclusion and Recommendation The results of this study can be applied for nursing care to patients with lumbar spondylosis disease undergoing spinal surgery. These tasks can be done by organizing preoperative education activities, discharge counselling activities, home visit calls, and outpatient department follow-up visits.